Perbedaan Penghasilan Nasabah Bank Sampah Induk Panca Daya dan Nasabah Induk Sakinah di Kota Padang - Risyafitri, Annisa; Irianto, Agus (Universitas Negeri Padang, 2024)
The purpose of this study was to analyze 1) Differences in waste savings income of Panca daya and Sakinah main waste bank customers to compare the performance of main waste bank in Padang city in increasing customer participation in waste sorting. 2) Differences in customer waste savings income based on the type of plastic and paper waste to compare the effectiveness of waste management in increasing the economic value of plastic and paper waste. This research was conducted using primary data. Type of data is kuantitatif comparative.The sample in this research was 89 respondents who were customers in the Panca daya and Sakinah main waste bank program using the proportional stratified random sampling method. Data collection was carried out by means of documentation and observation.. The data analysis technique used is two-way ANOVA. The findings of this study (1) There are a differences in customer’s waste savings income between Panca daya and Sakinah main waste bank , (2) There are differences in customer’s waste savings income based on the type of plastic and paper waste